Украшения в погребальном обряде срубной культуры: социальный и половозрастной аспект - Цимиданов, В.В. (Археологический альманах, 2004)
There are numerous burials with adornments among the complexes of the Timber-Grave community. They contain the temple's pendants, necklaces, bracelets, rings, compound bracelets, plait adornments, combs and clothing adornments, among others. The author has analysed 270 burials with adornments. Several conclusions were made, the most important of them the following: a) temple’s pendants and necklaces were worn both men and women. Bracelets, adornment sets consisting of several units were worn by women, but the combs were worn by men; b) plait adornments were a sign of the high social position in the eastern part of the Timber-Grave community territory. Adornment sets consisting of several units were the sign of the high social position in the west of the community’s territory: c) the social role of the person conditioned the type of the adornments worn; d) only a few of the dead were buried with adornments; more often the adornments were passed to the heirs.